2013
DOI: 10.15517/rbt.v61i2.11162
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity, reproductive seasonality and maturation size of <i>Callinectes sapidus</i> females (Decapoda: Portunidae) in the Southeast coast of Brazil

Abstract: C. sapidus fisheries has a significant influence on the economy of some countries in North America and has a relative extensive literature in these regions. However, only few papers discuss the ecology of C. sapidus in the South Atlantic, despite its economic importance in that region. We studied the fecundity, reproductive seasonality and maturation size of C. sapidus females captured in the Southeast coast of Brazil from January to December 2002. Females were separated, weighted (Wt), and cephalothorax width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
13
1
1
Order By: Relevance
“…This is the first documentation of extensive small-scale regional plasticity in blue crab size at maturity for the Gulf of Mexico. Coastwide size at 50% maturity was slightly less than that reported elsewhere (Guillory and Hein 1996;Severino-Rodrigues et al 2013), including that reported by Fisher (1999) from the Texas coast more than 2 decades earlier. This regional variation across Texas bays was observed with no apparent latitudinal trends.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This is the first documentation of extensive small-scale regional plasticity in blue crab size at maturity for the Gulf of Mexico. Coastwide size at 50% maturity was slightly less than that reported elsewhere (Guillory and Hein 1996;Severino-Rodrigues et al 2013), including that reported by Fisher (1999) from the Texas coast more than 2 decades earlier. This regional variation across Texas bays was observed with no apparent latitudinal trends.…”
Section: Discussioncontrasting
confidence: 59%
“…The minimum size limit (127 mm carapace width [CW]) in Texas is designed to allow female crabs the opportunity to spawn at least once before becoming vulnerable to harvest. Previous studies report size at 50% maturity for female blue crabs at 120 mm CW in Texas (Fisher 1999) and Chesapeake Bay (Rugolo et al 1997), 125 mm from Caillou Lake estuary, Louisiana (Guillory and Hein 1996), 122 mm in southeast Brazil (Severino-Rodrigues et al 2013), and 119 mm in the southwestern coast of Turkey (Sumer et al 2013). Tagatz (1968) reported that 40.5% of females at 130-134 mm CW were mature and only 18.5% of females at 125-129 mm.…”
mentioning
confidence: 97%
“…The mean fecundity in the presesnt study was lower. Variations in fecundity may have been caused by several factors such as the technique used for counting eggs, time and stage of embryonic development of eggs at the time of counting and genetic characteristics of the populations (Severino-Rodrigues et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile crabs were found in the benthic population almost throughout the year. Severino-Rodrigues et al (2013) reported that ovigerous females were more abundant between December and March in the Southest coast of Brazil. Tagatz (1968) found that spawning of blue crab occurred one or two months after mating during spring and summer in the St. Johns River in the northeastern Florida.…”
Section: Discussionmentioning
confidence: 99%